Museum Critique in Contemporary Artistic Practices: Collecting, Captioning, Displaying, Exhibiting - Adrian Fix (Miranda: Revue Pluridisciplinaire du Monde Anglophone, 2025)
This article presents a case study of the work of a contemporary artist, Ed Atkins, whose practice is based on the collection and arrangement of objects and the production of critical texts about them. His work reproduces the structural mechanisms of museum exhibitions and echoes the way in which cultural institutions build up their collections and present them to visitors. This article examines the extent to which contemporary artistic practices, now aware of the power mechanisms of cultural institutions, echo and critique them. It also provides an initial assessment of the principles for rethinking the museum developed by New Museology in the 1980s.